Study Tentang Dampak K3 dan Lingkungan Kerja pada Kinerja Karyawan Bagian Produksi - Andrean Eko Haryoko (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To analyze the influence of Occupational Safety and Health and the work environment on employee performance in a company.. Background Problems: The company has a disciplined work system and supervision of employees within the company that needs to be improved and encouraged by a conducive work environment. Novelty: Reexamining previous research on different companies and the time of the research. Research Methods: Using quantitative descriptive methods with SPSS as a tool in measuring the variables studied and using several methods in testing.. Finding/Results: There is a significant influence between K3 and the work environment on employee performance, and simultaneously there is a significant influence on increasing employee performance. Conclusion: It is best to monitor how K3 employees work in their workplace. Starting from occupational safety and occupational health of employees in the workplace and paying attention to the work environment of employees in their workplace. Starting from the physical work environment and non-physical work environment in the workplace. Because many employees still don't feel that the work environment at the company is good for them.